Development and performance evaluation of an effective dryer for poundo yam flour processing plant. Issue 1 (1st January 2017) - Ayodeji, S.P.; Ajamu, T.A.; Akinnuli, B.O.; Aderoba, O.A.
Abstract: The process of making pounded yam, from yam, Dioscorea spp., which is mostly consumed by people of sub-Sahara region as source of carbohydrate is energy consuming, therefore, the pounded yam flour, commonly called poundo yam, through which pounded yam is prepared faster and easier, has become popular in West Africa. Although there is an existing niche market for the design and production of poundo yam processing plant, proper drying, one of the most important stages in the production line of poundo yam flour is drying to remove moisture from parboiled (a stage before drying) yam chips still remains the limitation to an effective application of the processing plant in the food industry. The development and performance evaluation of an effective drier that will allow the movement of the dried yam chips to the next machine in poundo yam process plant and its suitability to the food industrial applications was carried out in this research. The volume of the drying drum was estimated to be 0.03 m 3 . The capacity of the dryer is the amount of yam the drying drum can contain per batch. 28 kg of yam chips was dried at a temperature of 50°C for 3.7 h being the safe drying temperature. The efficiency of the machine was evaluated by estimating the moisture removal rate from the yam in comparison with the power consumption rate and this gave 72.71%.